Spatial arrangement of the animal male germ cell genome: I. Non-random pattern of radiation-induced inversions involving the vestigial region in autosome 2 of Drosophila melanogaster - Alexandrov, Igor; Alexandrova, Margarita V.; Korablinova, Svetlana V.; Korovina, Larisa N. (İstanbul Kültür Üniversitesi, 2007)
At present, given a bulk of models for higher-order chromatin structure in interphase nuclei of animal somatic cells, little is known about the spatial chromosome organization in animal male germ cells mainly due to the lack suitable methods for detailed observation and analysis without disruption of the existing organization. We pioneered in the study of this issue via analysis of radiation-induced inversion patterns in Drosophila male germ cell genome taking into account the fact that the formation of inversion requires the spatial proximity and contact of its ends. Analysis of 72 γ- ray- or neutron-induced vg inversions in which the first break is invariantly associated with the vestigial (vg) gene in the middle of 2R autosome shows the second inversion breakpoints that highly non-randomly distributed over the entire second chromosome clustering at the three autosome 2 “hot” chromosome areas. These findings show that the polar Rabl-configuration of interphase chromosomes in various somatic cells is not typical for the haploid genome of Drosophila mature sperms. The specific megarosetteloopstructure of haploid chromosome in the mature animal sperms is proposed and justified.
Keywords: radiation; inversions; sperm genome; Drosophila; Chromosome folding arrangement; radyasyon; sperm genom; inversiyonlar; Kromozom katlama aranjman